2016
DOI: 10.1177/1756283x16645049
|View full text |Cite
|
Sign up to set email alerts
|

The role of antioxidants and zinc in minimal hepatic encephalopathy: a randomized trial

Abstract: Antioxidant and zinc supplementation can improve MHE in patients with liver cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 26 publications
0
49
2
Order By: Relevance
“…5 , 9 , 16 - 19 In one study Mosua N et al found improvement of minimal hepatic encephalopathy in cirrhosis after zinc supplementation. 21 Therefore, it can be proposed that zinc supplementation may reduce hepatic encephalopathy by improving the effectiveness of the urea cycle.…”
Section: Discussionmentioning
confidence: 99%
“…5 , 9 , 16 - 19 In one study Mosua N et al found improvement of minimal hepatic encephalopathy in cirrhosis after zinc supplementation. 21 Therefore, it can be proposed that zinc supplementation may reduce hepatic encephalopathy by improving the effectiveness of the urea cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperammonemia plays a major role in the development of brain edema and in evoking changes in cerebral blood flow (CBF) [13]. There are several drugs and clinical trials that could benefit patients with HE and most of them tend to reduce the production and absorption of ammonia from the colon, with the hypothesis that the colon is the primary organ that generates ammonia [14]. Recently, it was recorded that lactulose is the most commonly utilized nonabsorbable disaccharide for prophylaxis of HE [15].…”
Section: Discussionmentioning
confidence: 99%
“…Zinc is also required for detoxification of ammonia via the urea cycle in the liver and its serum level shows a significant inverse relationship with blood ammonia concentrations in LC patients [108]. Since zinc is closely related to the pathogenesis of HE, several studies have examined the effects of zinc supplementation in patients with HE and hyperammonemia [109][110][111][112]. Our research group has recently performed a prolonged, randomized, placebo-controlled, double-blind trial and found that zinc supplementation for three months is effective and safe in treating hyperammonemia in patients with LC [113].…”
Section: Other Ammonia-lowering Drugsmentioning
confidence: 99%